2012
DOI: 10.1074/jbc.m112.351817
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-selective and Calcium-independent Activation of CaMKII by α-Actinin

Abstract: Background: Synaptic signaling is modulated by protein-protein interactions involving receptor ion channels, cytoskeletal proteins, and protein kinases. Results: ␣-Actinin enhances CaMKII signaling to GluN2B-NMDARs, but interferes with CaMKII signaling to GluA1-AMPARs. Conclusion: CaMKII actions on key synaptic targets can be differentially modulated by a Ca 2ϩ -independent interaction with ␣-actinin. Significance: These findings provide new molecular insights into the synaptic mechanisms underlying learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 62 publications
7
53
0
Order By: Relevance
“…Here, we show that neither synaptic translocation nor CaMKII/GluN2B binding requires kinase activity. These shared characteristics strengthen the idea that GluN2B is both necessary and sufficient for CaMKII synaptic translocation, although additional mediating factors may contribute (Colbran and Brown, 2004;Jalan-Sakrikar et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
“…Here, we show that neither synaptic translocation nor CaMKII/GluN2B binding requires kinase activity. These shared characteristics strengthen the idea that GluN2B is both necessary and sufficient for CaMKII synaptic translocation, although additional mediating factors may contribute (Colbran and Brown, 2004;Jalan-Sakrikar et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
“…Work in the CNS has shown that CaMKII can interact with other proteins by diverse mechanisms (29,30). Our data show that CaMKII also interacts with the caspase 2-PP1 complex.…”
Section: Discussionmentioning
confidence: 56%
“…In immature motile protrusions, dissociation of this complex by group 1 mGluR activation may transiently decrease the proportion of CaMKII␤ bound to F-actin and enable protrusive motility and elongation. Actinins participate in the targeting of CaMKII␣ to F-actin (63), and CaMKII␤ knockdown reduces dendritic protrusion motility (43), similar to Actn4 down-regulation. Importantly, CaMKII-mediated effects on spine morphogenesis depend on its interaction with F-actin and not on its enzymatic activity (42).…”
Section: Discussionmentioning
confidence: 93%